Physiological Effects and Economic Impact of Plant Growth Regulator Applications on Soybean - Brenna Cannon; Hannah Shear; Colton Johnson; Josie Rice; Josh Lofton (Agronomy)
Soybean production in the southern Great Plains (SGP) faces challenges due to yield-limiting factors, including high temperatures and inconsistent precipitation. These conditions can lead to excess vegetative growth, similar to what occurs in crops like cotton. Management strategies utilizing plant growth regulators (PGRs) have been applied to control this excessive growth, yet there is limited information on methods to mitigate vegetative growth in soybeans through modifications to the apical meristem. Field trials conducted in 2022 and 2023 investigated the effects of altering the apical growth using Ascend SL, Compact, Cobra, Cygin Pro, and physical removal, with treatments applied at the V4 and R2 growth stages. This study highlights the significance of customized application strategies to enhance profitability under diverse environmental conditions. Ascend and Cygin Pro demonstrate improving yield stability under adverse climatic conditions. Both applications of Compact produced relatively stable yields across site years, while Cobra and physical removal methods necessitate careful consideration of timing to minimize yield losses. Further research is essential to optimize these management strategies for soybean production in the SGP.